Utilization of Postnatal Care Services Among Postpartum Mothers in Ogidi Community, Anambra State, Nigeria - Juliet Tochukwu Nwani (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
Background: Postnatal care (PNC) is a critical stage in the continuum of maternal and child health and it is often described as the fourth trimester due to its importance in determining lasting health outcome. Regardless of it pivotal role, the uptake level of postnatal service for both mothers and child remain suboptimal. This study aim was to describe the assessment of PNC service Utilization among postpartum mothers in Ogidi, Anambra State. Methods: A descriptive cross- sectional design was employed for this study. Data was collected using questionnaire, total of 501 questionnaires was distributed and 440 was accurately completed and returned, giving an 87.8% rate of response. A multi stage sampling technique was used to determine a sample size of 440 postpartum mothers. SPSS version 26 was used to analysis the uptake level for mothers showing the frequency Results: Results shows that 292 mothers (66.4%) utilized PNC services after their most recent delivery. Among them, 42.1% attended one visit, 30.8% attended two visits, and 27.1% attended three or more visits. Infant PNC uptake was also 66.4%, with most first visits occurring within 3 7 days (42. 8%). The barriers and facilitators to postnatal care services utilisation was analyzed and presented in a table showing the mean, median and standard deviation. Conclusion: This study shows that the utilization of PNC services in Idemili North Local Government of Anambra State is influenced by complex interaction of cultural, personal, socio economic and health system factors. Therefore, to strengthen the use of postnatal care, it requires increased awareness and also addressing structural and behavioral barriers.